2017
DOI: 10.1002/ecs2.1745
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimentally reduced snowpack and passive warming on montane meadow plant phenology and floral resources

Abstract: Abstract. Climate change can have a broad range of effects on ecosystems and organisms, and early responses may include shifts in vegetation phenology and productivity that may not coincide with the energetics and forage timing of higher trophic levels. We evaluated phenology, annual height growth, and foliar frost responses of forbs to a factorial experiment of snow removal (SR) and warming in a high-elevation meadow over two years in the Rocky Mountains, United States. Species included arrowleaf balsamroot (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 51 publications
(57 reference statements)
6
55
0
1
Order By: Relevance
“…Snow removal has been shown to be an effective way to induce early flowering in plants (Gezon et al, ; Wipf, ). Although snow removal could affect soil moisture, few studies have documented any significant differences in soil moisture between snow removal and natural snowmelt treatments (Wipf, , but see Sherwood, Debinski, Caragea, & Germino, ). Plots in the frost treatment were exposed to naturally occurring frost events, while plots in the frost‐reduction treatment were covered with frost‐resistant tarps (Easy Gardener Products, Waco, TX) the evening before a frost event was forecasted to occur, and tarps were removed the following morning once temperatures reached above 0°C.…”
Section: Methodsmentioning
confidence: 99%
“…Snow removal has been shown to be an effective way to induce early flowering in plants (Gezon et al, ; Wipf, ). Although snow removal could affect soil moisture, few studies have documented any significant differences in soil moisture between snow removal and natural snowmelt treatments (Wipf, , but see Sherwood, Debinski, Caragea, & Germino, ). Plots in the frost treatment were exposed to naturally occurring frost events, while plots in the frost‐reduction treatment were covered with frost‐resistant tarps (Easy Gardener Products, Waco, TX) the evening before a frost event was forecasted to occur, and tarps were removed the following morning once temperatures reached above 0°C.…”
Section: Methodsmentioning
confidence: 99%
“…Snow melt timing has been recognized as early as the 1930s as a primary initiator of plant phenological events in both Arctic and alpine tundra (Schwartz, 2013;see, e.g., Billings & Mooney, 1968;Sørensen, 1941;Wipf & Rixen, 2010), and many recent studies have demonstrated that snow melt date is a key driver explaining variation in spring phenology in tundra ecosystems (Bjorkman et al, 2015;Cooper, Dullinger, & Semenchuk, 2011;Cortés et al, 2014;Iler et al, 2017;Molau et al, 2005;Semenchuk et al, 2016;Sherwood, Debinski, Caragea, & Germino, 2017;Wipf, 2009;Wipf, Stoeckli, & Bebi, 2009; but see Thórhallsdóttir, 1998). During snow melt, tundra plants experience dramatic changes in their immediate environment: light availability increases and plant and soil surfaces are exposed to atmospheric temperatures and CO 2 concentrations (Starr & Oberbauer, 2003), which in turn stimulate plant metabolic and developmental activities (Jones, 2013).…”
Section: Snow Melt As a Drivermentioning
confidence: 99%
“…In addition, snow melt may act as an indicator for suitable growing conditions to come as the growing season advances (Wheeler et al, 2015). Prior to melt, the insulation of the snow layer protects the plants from frost damage, desiccation and photoinhibition (Lundell, Saarinen, & Hänninen, 2010;Mølgaard & Christensen, 2003;Sherwood et al, 2017;Wheeler et al, 2015;Wipf & Rixen, 2010;Wipf et al, 2009) and reduces early-season herbivory (Wheeler et al, 2016), while after snow melt, the availability of soil moisture and nutrients is increased (Wipf & Rixen, 2010). Plants may therefore experience strong evolutionary pressure to adapt spring metabolic activity to coincide directly with the timing of snow melt (Cortés et al, 2014).…”
Section: Snow Melt As a Drivermentioning
confidence: 99%
“…Pikas are diet generalists that consume forbs, graminoids, and foliage of shrubs and trees (Dearing 1996). Experimental snow removals alter plant phenology and increase exposure to frost damage (Sherwood et al 2017), which can change composition and abundance of vegetation. Bhattacharyya and Ray (2015) observed significant changes in haypile composition that coincided with a trend in earlier melt-off in the southern Rockies, where amounts of vegetation high in secondary metabolites decreased as snow melt occurred earlier.…”
Section: Direct Vs Indirect Mechanismsmentioning
confidence: 99%